2006
DOI: 10.1111/j.1365-294x.2005.02968.x
|View full text |Cite
|
Sign up to set email alerts
|

Parallelism in gene transcription among sympatric lake whitefish (Coregonus clupeaformisMitchill) ecotypes

Abstract: We tested the hypothesis that phenotypic parallelism between dwarf and normal whitefish ecotypes (Coregonus clupeaformis, Salmonidae) is accompanied by parallelism in gene transcription. The most striking phenotypic differences between these forms implied energetic metabolism and swimming activity. Therefore, we predicted that genes showing parallel expression should mainly belong to functional groups associated with these phenotypes. Transcriptome profiles were obtained from white muscle by using a 3557 cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
197
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(211 citation statements)
references
References 59 publications
11
197
0
3
Order By: Relevance
“…For example, parallel locus-specific reductions in gene flow for growth QTL have been found between dwarf and Normal ecotypes among independently diverging populations, indicating that growth differences among populations are maintained by divergent selection (Rogers and Bernatchez 2005). Evidence for parallel evolution indirectly demonstrated the role of divergent selection in maintaining differentiation between sympatric whitefish ecotypes for several traits, including morphology, behavior, as well as gene expression associated with swimming efficiency and energy metabolism Rogers et al 2002;Derome et al 2006). As such, understanding the consequences of population divergence in the lake whitefish will benefit from a population genomics approach that embraces a genomewide search for the genetic basis of phenotype-environment associations (Luikart et al 2003;Schö tterer 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, parallel locus-specific reductions in gene flow for growth QTL have been found between dwarf and Normal ecotypes among independently diverging populations, indicating that growth differences among populations are maintained by divergent selection (Rogers and Bernatchez 2005). Evidence for parallel evolution indirectly demonstrated the role of divergent selection in maintaining differentiation between sympatric whitefish ecotypes for several traits, including morphology, behavior, as well as gene expression associated with swimming efficiency and energy metabolism Rogers et al 2002;Derome et al 2006). As such, understanding the consequences of population divergence in the lake whitefish will benefit from a population genomics approach that embraces a genomewide search for the genetic basis of phenotype-environment associations (Luikart et al 2003;Schö tterer 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, postglacial parallel phenotypic evolution of sympatric pairs ) exhibits bimodal adult size distributions whereby divergent selection for differential growth has maintained and promoted sympatric divergence between dwarf and Normal populations associated with the use of distinct limnetic and benthic trophic niches (Chouinard et al 1996;Campbell and Bernatchez 2004;Rogers and Bernatchez 2005). Altogether, these populations display adaptive trait differentiation with respect to life history , behavioral (Rogers et al 2002), physiological (Rogers and Bernatchez 2005), transcriptional (Derome et al 2006), and morphological traits Rogers et al 2002;Bernatchez 2004). A linkage mapping approach in young diverging populations of the lake whitefish could: (1) substantially improve our understanding of the genetic architecture of historically contingent and adaptive trait differences contributing to the population divergence between species and (2) help in identifying genomic regions permeable or resistant to gene flow.…”
mentioning
confidence: 99%
“…RNA-seq was used to study salinity tolerance in Arctic charr, linking expression and quantitative trait loci 16 . Microarray studies of adult lake whitefish ( Coregonus clupeaformis ) pointed to parallel expression differences between benthic and limnetic forms 17 . Filteau et al (2013) 18 found that a set of coexpressed genes differentiated the two whitefish morphotypes, implicating Bone morphogenesis protein (BMP) signaling in the development of ecological differences in tropic morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the validity of this array has been amply demonstrated in lake whitefish, whereas hybridization signal is the same as for Atlantic salmon (von Schalburg et al, 2005). Sequence divergence between normal and dwarf is also very low and therefore did not affect hybridization kinetics (Derome et al, 2006;Whiteley et al, 2008). Samples of dwarf, normal, backcross-healthy and backcross-moribund were hybridized in a loop design, involving eight biological replicates for the backcross-healthy and backcrossmoribund comparison and six for the others.…”
Section: Experimental Designmentioning
confidence: 99%